Reverse‐phase chiral high‐performance liquid chromatography for separation of a diastereomer in alalevonadifloxacin: A novel antibacterial agent. (7th February 2021) - Ahirrao, Vinod; Rane, Vipul; Patil, Kiran; More, Kiran; Jadhav, Rajiv; Yeole, Ravindra
Abstract: Alalevonadifloxacin (ALA) is a novel antibacterial drug, recently launched in India to treat infections caused by Gram‐positive bacteria. In present work, a chiral high‐performance liquid chromatographic method was developed and validated for the quantification of a diastereomeric impurity (DI) in ALA. The separation was achieved on Pirkle type ( R, R ) Whelk‐O1 chiral stationary phase, using ammonium formate buffer and acetonitrile in gradient fashion at a flow rate of 1.5 ml/min. The method was extensively validated for the quantification of DI in ALA. The detector response for DI was linear over the concentration range of 0.24–4.78 μg/ml. Limit of quantitation and limit of detection for DI were 0.24 and 0.07 μg/ml respectively. The mean recovery of the DI was 103.47 ± 5.14%. The impact of column temperature on the chiral separation was evaluated. The method was employed for controlling diastereomeric impurity in the batches of ALA used in preclinical studies.